2018
DOI: 10.21608/asnj.2018.59651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teaching Program on Nurse`s Performance Regarding Guillian Barre Syndrome Patients at Neurological Care Unit.

Abstract: Aim of the study: the study was aimed to evaluate the effect of teaching program on nurse`s performance regarding Guillian Barre Syndrome patients at neurological Care Unit at Assuit University Hospital. Research design: Quasi experimental research design was utilized in the study. Subject and method: the study was carried out on a convenience 30 nurses who participating in Guillian Barre patient care. One tool have been utilized to gather the information, tool I structure questionnaire divided into three part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…The current study indicated statistically significant improvement in total knowledge and practice over time. This finding was inconsistence with another study finding conducted by Abdelmonem et al (9) who stated that nurses had unsatisfactory knowledge pre teaching program compared to post teaching program. The majority of nurses' practice have been inadequate pre teaching program compared with post teaching program.…”
Section: Discussioncontrasting
confidence: 92%
“…The current study indicated statistically significant improvement in total knowledge and practice over time. This finding was inconsistence with another study finding conducted by Abdelmonem et al (9) who stated that nurses had unsatisfactory knowledge pre teaching program compared to post teaching program. The majority of nurses' practice have been inadequate pre teaching program compared with post teaching program.…”
Section: Discussioncontrasting
confidence: 92%